Fipronil recognition by the FA1 site of human serum albumin. Issue 8 (15th April 2018) - Ascenzi, Paolo; Leboffe, Loris; Toti, Daniele; Polticelli, Fabio; Trezza, Viviana
Abstract: Fipronil is a broad‐spectrum pesticide widely used in agriculture, horticulture, and forestry. Because fipronil can cause a variety of toxic effects in animals and humans, its use is authorized as a pesticide in veterinary medicinal products for pets, but not for the treatment of livestock animals whose products are intended for consumption. Recently, however, the presence of fipronil residues has been detected in the eggs and meat of layer hens from farms located in different European countries. Given the relevance of fipronil toxicity for human health, it is important to gain information concerning its fate in the human body, including its binding mode to human serum albumin (HSA), the most abundant protein in plasma. Here, the inhibition of heme‐Fe(III) binding to the fatty acid site 1 (FA1) of HSA by fipronil is reported. Docking simulations support functional data, indicating that the FA1 site is the preferential cleft for fipronil recognition by HSA. The affinity of fipronil for HSA ( K f  = 1.9 × 10 −6  M, at pH 7.3, and 20.0°C) may be relevant in vivo. Indeed, HSA could play a pivotal role in fipronil transport and scavenging, thus reducing the pesticide‐free plasmatic levels, with consequent reduced systemic toxicity. In turn, fipronil binding to the FA1 site of HSA could impair the recognition of endogenous and exogenous molecules. Abstract : Fipronil is a broad‐spectrum pesticide causing variety of toxic effects in humans. It binds preferentially to the FA1 site of human serum albumin inhibiting competitively heme‐Fe(III) recognition. HSA could play a pivotal role in fipronil scavenging reducing systemic toxicity.